2017
DOI: 10.1021/acs.jpcc.7b05725
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Catalytic Activity of Cerium Oxide Nanoparticles with the Anion of the Precursor Salt

Abstract: In this work, we tested our hypothesis that surface chemistry and antioxidant properties of cerium nanoparticles (CNPs) are affected by presence of counterions. We first employed various precursor cerium (III) (Ce(III)) salts with different counterions (acetate, nitrate, chloride, sulfate) to synthesize CNPs following the same wet chemical methodology. Electron spin resonance (ESR) studies provided evidence for the formation of radicals from counterions (e.g., NO3•2− from reduction of NO3− in CNPs synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Cerium oxide NPs increased ROS production in pancreatic cancer cells, resulting in the activation of thioredoxin 1 (TRX1)-apoptosis signaling kinase 1 (ASK1)-c-Jun terminal kinase (JNK) (TRX1-ASK1-JNK) redox-sensing pathway and apoptosis [48]. In contrast, another work showed that cerium nanoparticles (CNPs) exhibited higher SOD-mimetic activity, which could be modulated by the change in the anion of the precursor salt [55]. CuO NPs (5.4 nm) significantly increased oxidative stress levels, resulting in radiosensitization effects in MCF-7 cells and U14 tumor-bearing nude mice [49].…”
Section: Nanoradiosensitizers Based On Oxidative Stressmentioning
confidence: 99%
“…Cerium oxide NPs increased ROS production in pancreatic cancer cells, resulting in the activation of thioredoxin 1 (TRX1)-apoptosis signaling kinase 1 (ASK1)-c-Jun terminal kinase (JNK) (TRX1-ASK1-JNK) redox-sensing pathway and apoptosis [48]. In contrast, another work showed that cerium nanoparticles (CNPs) exhibited higher SOD-mimetic activity, which could be modulated by the change in the anion of the precursor salt [55]. CuO NPs (5.4 nm) significantly increased oxidative stress levels, resulting in radiosensitization effects in MCF-7 cells and U14 tumor-bearing nude mice [49].…”
Section: Nanoradiosensitizers Based On Oxidative Stressmentioning
confidence: 99%
“…However, metal precursor salts in the synthesis gel could cause changes in the assembly of CTA + molecules, leading to less organized materials when compared to Si-MCM-41. As Barkam and co-workers [52] demonstrated, even the use of different anions for the same metal precursor can extensively affect the physicochemical properties of particles in solution [52].…”
Section: X-ray Fluorescence (Xrf) and X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…As for Ce-MCM-NO 3 , part of the cerium added in the synthetic medium does not react with silicate oligomers and precipitates to form non-framework [Ce(OH) 3 ], which converts completely to CeO 2 after calcination. Such a hypothesis is scarcely pointed out to explain the difference in the reactivity of cerium precursors in the synthesis of oxides, but there is an extensive literature regarding the differences in the use of precursors that leads to singular microstructural properties of these materials [52,76,77]. These works clearly suggest that the anions in cerium precursors have major roles in defining the properties of the final cerium-based materials more than just the mere electrostatic counterparts in the synthetic medium.…”
Section: Spectroscopy Studies (Ftir Uv-vis Raman and 29 Si Mas-nmr)mentioning
confidence: 99%
“…Many of these complications can be summarized as follows: (1) synthesis processes are often highly sensitive to subtle variations in unexpected ways and not easily reproducible and (2) nano‐objects are unstable, easily damaged during handling, storage, and analysis, and frequently change as a function of time or environment . Seemingly minor variations in synthesis, age or source of precursor chemicals, processing, or storage have been found to produce nano‐objects with significantly different properties or lifetimes …”
Section: Introductionmentioning
confidence: 99%
“…1,9,19 Seemingly minor variations in synthesis, age or source of precursor chemicals, processing, or storage have been found to produce nanoobjects with significantly different properties or lifetimes. [20][21][22][23] The significant impact of seemingly minor changes in sample preparation on properties, along with the ease of sample transformation due to environmental changes, complicates the ability of experiments to be reproduced. This sensitivity highlights the importance of knowledge of sample history and appropriate characterization in providing important information about a sample and the impacts of analysis.…”
mentioning
confidence: 99%